Trial, Error, and Expertise: My Evolution Through Structural and Preservation Rhinoplasty Techniques - Çakır, Barış; Coşkun, Erhan (Facial Plastic Surgery, 2025)
Rhinoplasty continues to evolve, with small technical refinements yielding significant aesthetic and functional gains. This article reflects on nearly two decades of surgical experience, focusing on the balance between structural support and anatomical preservation.The study aims to evaluate the effectiveness of combining preservation and structural techniques in closed rhinoplasty. It is hypothesized that this hybrid approach enhances surgical consistency and long-term outcomes.A retrospective, experience-based review of a single surgeon's rhinoplasty evolution is presented, highlighting technical transitions and refinements over time.Key refinements include Pitanguy ligament preservation, controlled mucosal resection, scroll area preservation, dual-plane dissection, rim flap techniques, subdomal grafting, and wide subperiosteal dissection. Open and closed approaches were selected based on anatomical features and case complexity.The adoption of preservation principles in closed rhinoplasty led to improved tip definition, supratip contour control, and dorsal stability. Wide dissection techniques enhanced skin redraping and minimized postoperative complications. Combining structural support with anatomical preservation yielded more predictable outcomes in primary cases.Closed rhinoplasty techniques that integrate both preservation and structural strategies offer a reproducible and refined surgical result. Continuous evaluation and adjustment of technical details are key to optimizing long-term functional and aesthetic success.
Keywords: rhinoplasty; preservation rhinoplasty; closed rhinoplasty